The Influence Of Financial Knowledge, Financial Attitudes, And Peer Influence On The Consumptive Behaviour Of Generation Z In Bengkulu City - Anggraini, Adinda Dewi; Anggriani , Ida; Kurniawan, Kimas (Journal of Accounting and Management, 2025)
This study aims to examine the influence of financial knowledge, financial attitude, and peer influence on consumptive behavior among Generation Z in Bengkulu City. This research employs a quantitative approach using primary data collected through questionnaires distributed to 180 Generation Z respondents in Bengkulu City. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 26.The results show that partially, financial knowledge (X₁) has a negative and significant effect on consumptive behavior, financial attitude (X₂) has a positive and significant effect on consumptive behavior, and peer influence (X₃) has a positive and significant effect on the consumptive behavior of Generation Z in Bengkulu City. Simultaneously, these three variables have a significant effect on consumptive behavior. The coefficient of determination (R²) value of 0.390 indicates that 39% of the variation in consumptive behavior can be explained by financial knowledge, financial attitude, and peer influence, while the remaining 61% is influenced by other factors not examined in this study. The regression equation obtained is: Y = 13.212 – 0.207X₁ + 0.195X₂ + 0.492X₃ + 2,309. These findings indicate that higher levels of financial knowledge tend to decrease consumptive behavior, while more positive financial attitudes and stronger peer influence tend to increase the consumptive behavior of Generation Z in Bengkulu City.